New results on asymptotic properties of likelihood estimators with persistent data for small and large T - Artūras Juodis; Vasilis Sarafidis (SERIEs - Journal of the Spanish Economic Association, 2023)
This paper revisits the panel autoregressive model, with a primary emphasis on the unit-root case. We study a class of misspecified Random effects Maximum Likelihood (mRML) estimators when T is either fixed or large, and N tends to infinity. We show that in the unit-root case, for any fixed value of T, the log-likelihood function of the mRML estimator has a single mode at unity as . Furthermore, the Hessian matrix of the corresponding log-likelihood function is non-singular, unless the scaled variance of the initial condition is exactly zero. As a result, mRML is consistent and asymptotically normally distributed as N tends to infinity. In the large-T setup, it is shown that mRML is asymptotically equivalent to the bias-corrected FE estimator of Hahn and Kuersteiner (Econometrica 70(4):1639-1657, 2002). Moreover, under certain conditions, its Hessian matrix remains non-singular.
Keywords: C13; C33; 330; Dynamic panel data; Maximum likelihood; Monte Carlo simulation